Pathways to sustainable waste management in Indian Smart Cities - V. R. Sankar Cheela; Ved Prakash Ranjan; Sudha Goel; Michele John; Brajesh Dubey (Journal of Urban Management, 2021)
To develop intelligent and sustainable cities, the government of India launched initiatives like Smart Cities and the Clean Development Mission. Solid waste management (SWM) has become one of the primarily focused areas of such initiatives. The changing dynamics of urban waste characteristics due to unplanned urbanization and rapid growth in urban populations (due to migration) has been a significant concern for local authorities in urban areas to develop an effective SWM plan. The development of a long-term SWM plan along the line of the government initiatives' objectives requires understanding the waste quantities, characteristics, and existing waste management practices. This paper presents an overview of existing waste management activities, financial and institutional demographics in six selected Indian Smart Cities, and the field studies to assess SWM systems as per the waste management rules. The study involved a participatory approach to collect data from local bodies and stakeholders. Indicative strategies for the development of waste management systems were formulated based on the outputs of this analysis. Discussion on pathways includes waste characterization, funding sources, data technologies, and service level benchmarking to plan an integrated solid waste management system for a Smart City. The outcomes of this study shall equip local authorities in designing waste systems to accelerate the transition towards innovative and sustainable waste systems.
Keywords: 710; Solid waste management; Smart cities; Waste management index; Source segregation; Clean India Mission